IMF Staff Papers, Volume 47, No. 1. (IMF Staff Papers; IMF Staff Papers, 2000)
This paper discusses the origins of the pyramid schemes and the way the authorities handled them. The paper analyzes the economic effects of the pyramid schemes, concluding that despite the descent into anarchy triggered by the schemes' collapse, their direct effects on the economy are difficult to specify and appear to have been limited. The paper also argues that prevention of pyramid schemes is better than cure and that government and international financial institutions should be vigilant in clamping down on frauds.